Molecular characterization of Methylmalonyl CoA mutase deficiency in patients identified through newborn screening - Marcão, Ana (2013)
Methylmalonyl CoA mutase (MCM) deficiency due to mutations in MUT gene is a rare metabolic disorder with autosomal recessive inheritance. Based on the complete or partial absence of functional apoenzyme, two distinct biochemical phenotypes can be associated with MCM deficiency: mut0 and mut- forms, respectively. Patients presenting the mut0 form often develop, already in the first days of live, severe clinical symptoms resulting from rapidly progressing metabolic acidosis. From the genetic point of view this is an heterogeneous condition, with most mutations present in single families. In spite of this heterogeneity, several mutations were found to be frequent, some of them among specific ethnic groups. Since the inclusion of MCM deficiency in the Portuguese Newborn Screening in 2005, approximately 715 000 newborns have been tested and only three were found to have MCM deficiency, thus confirming the low frequency of this disease (1:238 333). These patients were identified through elevated C3 (propionylcarnitine) and C3/C2 ratio, and they all presented a severe clinical phenotype. Molecular study was done by sequencing whole coding sequence and exon-intron flanking regions, after PCR amplification from genomic DNA. Four different mutations were identified in these patients. One of them (p.G717V) was reported to be frequent among black patients and two other (R108C and c.1022dupA) were previously found among patients of Hispanic origin. Mutation p.G626Efs*18 was found in two different patients, although their families don’t seem to be related. MCM deficiency is often a life threatening disease with neurological manifestations difficult to prevent with traditional therapies. Molecular characterization of MCM deficient patients is important, not only to elucidate the genetic epidemiology of the disease in Portugal, but also because novel therapies based on the genotype have recently been proposed for MCM deficiency.